Firm Innovation under Import Competition from Low-Wage Countries - Ujjayant Chakravorty; Runjuan Liu; Ruotao Tang (Center for Economic Studies and ifo Institute (CESifo), 2017)
In recent years, manufacturing firms in the United States have faced increasing import competition from low-wage countries, especially China. Does this competition hurt or help innovation by firms? This paper studies the effect of the surge in imports from China on innovation in the US manufacturing sector. We combine patent, firm and trade data during 1990-2006 for US publicly-listed firms in the Compustat dataset. We find consistent evidence that Chinese import competition had a positive effect on firm innovation, as measured by citation-weighted patent applications. This positive effect persists when we instrument import competition in the US by using Chinese import penetration in the United Kingdom. Next we investigate this relationship between import competition and innovation by considering industry and firm heterogeneity. We find that firms in low-tech industries and those with a lower degree of product differentiation show a significant positive response to import competition. Firms with a higher capital intensity and lower labor productivity also exhibit a greater response. These results are shown to be robust to a variety of measures for import penetration and innovation.
Keywords: F10; F14; O31; O32; 330; import competition; innovation; international trade; manufacturing firms; patents